Etiological analysis of patients with sudden sensorineural hearing loss: a prospective case–control study - Wen Xie; Niki Karpeta; Busheng Tong; Jiali Liu; Haisen Peng; Chunhua Li; Sten Hellstrom; Yuehui Liu; Maoli Duan (Scientific Reports, 2023)
Abstract Sudden sensorineural hearing loss (SSNHL) is a multifactorial emergency disease. Until now, the etiology of SSNHL is still unknown. Previous studies regarding the etiology of SSNHL are clinical studies depending on clinical data collection and analysis. Due to the insufficient sample size or various selective bias in clinical studies, the results of these studies may be inaccurate. This prospective case–control study aimed at exploring the possible etiology and risk factors of SSNHL. We enrolled 255 SSNHL patients and 255 sex-, age- and residence-matched non-SSNHL subjects in the control group. Our study shows that there was no significant difference in the prevalence of comorbidities including hypertension and diabetes, as well as the incidence of smoking and drinking habits between the case and control groups (P > 0.05). In addition, the peripheral blood white blood cell count, neutrophil count, platelet-to-lymphocyte ratio (PLR) and fibrinogen level of the case group were significantly higher than those in the control group (P < 0.05). These findings suggest smoking, drinking, hypertension and diabetes may not be related to the onset of SSNHL. However, hypercoagulable state and inner ear vascular microthrombosis related to an elevated fibrinogen level might be the risk factors of the disease. In addition, inflammation play an important role of SSNHL onset. Trial Registration: Chinese Clinical Trial Registry. Registration number: ChiCTR2100048991.